If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2x(x + 4) = 0 Reorder the terms: 4x + 2x(4 + x) = 0 4x + (4 * 2x + x * 2x) = 0 4x + (8x + 2x2) = 0 Combine like terms: 4x + 8x = 12x 12x + 2x2 = 0 Solving 12x + 2x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2x'. 2x(6 + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6Solution
x = {0, -6}
| -4x-6(-2+4)=64 | | 2x+y-z=7z | | -4x-6(-2+4)=64 | | 3x-1=-3x+3 | | 3x-1=-3x+3 | | -5x+-2=-2X+4 | | -6x-5(-3x-3)=60 | | 114=2x+3x | | 5x+7y=3890 | | 8x+7y-5-5x+6y-3= | | -2x-2(-5x-4)=-80 | | 15+4y-1=15y-13-2y | | y+(y-2)2=2 | | 3x-n=7+n | | 25-13=3(x-1) | | -13.9=b+17.1 | | r+7= | | 15-44=3(x-4)-5 | | 3x+(x-5)=15+4 | | -16+13=m-2 | | -3x=8-(-1) | | 3w+5-2w+7= | | 2x^6=-3 | | 5mn-2m(m-2n)= | | 7(x+2)-3x=4(x-1)+10 | | -13.9=b-17.1 | | 3(2n-m)+4m= | | -9x+7=16 | | 9X-2(8-X)=61 | | f(x+2)=9x-1 | | -(6-y+3)-(-5y-8)=2 | | e+73=7 |